Laboratory-scale additive content assessment for aluminum-silicate-based wood chip additivation. (February 2021) - Gollmer, Christian; Höfer, Isabel; Kaltschmitt, Martin
Abstract: This paper analyzes the aluminum-silicate-based additivation of wood chips with regard to the retention of the ash and particulate matter (PM) forming element potassium (K) in high-temperature stable ashes. In terms of additivation, two types of the aluminum-silicate-based additive kaolin are used. The wood-additive-samples are analyzed in detail with respect to the ash content, the recovery rate of the ash and PM forming element K, the crystalline phases of the high-temperature stable ashes and the achieved additivation efficiency by means of an experimental as well as a theoretical approach. Based on the obtained findings, a general suitability of wood chips for additivation can be derived. Thereby, assessing the additive content solely based on stoichiometric calculations considering the alkali element content in the biomass and applying generalized safety factors from the literature turned out to be not advisable during the present study. Instead, the presence of alkaline earth elements originating from the biomass and the actual additivation process need to be considered as well. Given the composition of the wood chips in the present study and the applied additivation process, advisable additive contents between 1.49 wt%a.r. and 3.53 wt%a.r. were determined based on theoretical calculations. Highlights: A general suitability of wood chips for additivation could be proven. The fuel composition is crucial for a proper additive content assessment. Additive losses might occur due to the additivation process. High ash incorporation of potassium could be achieved.